Microscopic characterization of Fe nanoparticles formed on SrTiO3(001) and SrTiO3(110) surfaces - Tanaka, Miyoko (Beilstein Journal of Nanotechnology, 2016)
Fe nanoparticles grown on SrTiO3 (STO) {001} and {110} surfaces at room temperature have been studied in ultrahigh vacuum by means of transmission electron microscopy and scanning tunnelling microscopy. It was shown that some Fe nanoparticles grow epitaxially. They exhibit a modified Wulff shape: nanoparticles on STO {001} surfaces have truncated pyramid shapes while those on STO {110} surfaces have hexagonal shapes. From profile-view TEM images, approximate values of the adhesion energy of the nanoparticles for both shapes are obtained.
Keywords: epitaxial orientation relationship; iron (Fe); nanoparticles; morphology; scanning electron microscopy (SEM); strontium titanate (SrTiO3); transmission electron microscopy (TEM); Wulff construction

(untitled) - Carvell, J.; Ayieta, E.; Garvin, A.; Cheng, R.; Shah, V. R.; Sokol, P. (J. Appl. Phys., 2010)

(untitled) - Rümmeli, M. H.; Schäffel, F.; Bachmatiuk, A.; Adebimpe, D.; Trotter, G.; Börrnert, F.; Scott, A.; Coric, E.; Sparing, M.; Rellinghaus, B.; MacCormick, P. G.; Cuniberti, G.; et al. (ACS Nano, 2010)

(untitled) - Zhou, Z.-Y.; Tian, N.; Li, J.-T.; Broadwell, I.; Sun, S.-G. (Chem. Soc. Rev., 2011)

(untitled) - Li, H.; Yin, S.; Wang, Y.; Sato, T. (J. Am. Ceram. Soc., 2013)

(untitled) - Kleibert, A.; Rosellen, W.; Getzlaff, M.; Bansmann, J. (Beilstein J. Nanotechnol., 2011)

(untitled) - Nillius, N.; Rienks, E. D. L.; Rust, H.-P.; Freund, H.-J. (Phys. Rev. Lett., 2005)

(untitled) - Torelli, P.; Soares, E. A.; Renaud, G.; Gragnaniello, L.; Valeri, S.; Guo, X. X.; Luches, P. (Phys. Rev. B, 2008)

(untitled) - Gavioli, L.; Cavaliere, E.; Agnoli, S.; Barcaro, G.; Fortunelli, A.; Granozzi, G. (Prog. Surf. Sci., 2011)

(untitled) - Novotný, Z.; Argentero, G.; Wang, Z.; Schmid, M.; Diebold, U.; Parkinson, G. S. (Phys. Rev. Lett., 2012)

(untitled) - Benedetti, S.; Stavale, F.; Valeri, S.; Noguera, C.; Freund, H.-J.; Goniakowski, J.; Nilius, N. (Adv. Funct. Mater., 2013)

(untitled) - Cho, G. B.; Yamamoto, M.; Kamada, Y. (Jpn. J. Appl. Phys., 2002)

(untitled) - Silly, F.; Castell, M. R. (Phys. Rev. Lett., 2005)

(untitled) - Zhang, Z.; Feng, J.; Wang, Z.; Yang, F.; Guo, Q.; Guo, J. (J. Chem. Phys., 2011)

(untitled) - Chien, T.; Freeland, J. W.; Guisinger, N. P. (Appl. Phys. Lett., 2012)

(untitled) - Sun, J.; Wu, C.; Silly, F.; Koós, A. A.; Dillon, F.; Grobert, N.; Castell, M. R. (Chem. Commun., 2013)

(untitled) - Vervisch, W.; Mottet, C.; Goniakowski, J. (Eur. Phys. J. D, 2003)

(untitled) - Land, X. Y.; Jiang, Q. (J. Nanopart. Res., 2007)

(untitled) - Wawro, A.; Sobańska, M.; Petroutchik, A.; Baczewski, L. T.; Pankowski, P. (Nanotechnology, 2010)

(untitled) - Harp, G. R.; Farrow, R. F. C.; Marks, R. F.; Vazquez, J. E. (J. Cryst. Growth, 1993)

(untitled) - Asthagiri, A.; Niederberger, C.; Francis, A. J.; Porter, L. M.; Salvador, P. A.; Sholl, D. S. (Surf. Sci., 2003)

(untitled) - Mukunoki, Y.; Nakagawa, N.; Susaki, T.; Wang, H. Y. (Appl. Phys. Lett., 2005)

(untitled) - Biswas, A.; Rossen, P. B.; Yang, C.-H.; Siemons, W.; Jung, M.-H.; Yang, I. K.; Ramesh, R.; Jeong, Y. H. (Appl. Phys. Lett., 2011)

(untitled) - Tanaka, M.; Takeguchi, M.; Yasuda, H.; Furuya, K. (J. Electron Microsc., 2002)

(untitled) - Kawasaki, M.; Takahashi, K.; Maeda, T.; Tsuchiya, R.; Shinohara, M.; Ishiyama, O.; Yonezawa, T.; Yoshimoto, M.; Koinuma, H. (Science, 1994)

(untitled) - Tanaka, M. (Appl. Surf. Sci., 2014)

(untitled) - Castell, M. R. (Surf. Sci., 2002)

(untitled) - Newell, D. T.; Harrison, A.; Silly, F.; Castell, M. R. (Phys. Rev. B, 2007)

(untitled) - Nishimura, T.; Ikeda, A.; Namba, H.; Morishita, T.; Kido, Y. (Surf. Sci., 1999)

(untitled) - Kubo, T.; Nozoye, H. (Surf. Sci., 2003)

(untitled) - Erdman, N.; Poeppelmeier, K. R.; Asta, M.; Warschkow, O.; Ellis, D. E.; Marks, L. D. (Nature, 2002)

(untitled) - Jiang, Q. D.; Zegenhagen, J. (Surf. Sci., 1999)

(untitled) - González, M. S. M.; Aguirre, M. H.; Morán, E.; Alario-Franco, M. A.; Perez-Dieste, V.; Avila, J.; Asensio, M. C. (Solid State Sci., 2000)

(untitled) - Ikeda, A.; Nishimura, T.; Morishita, T.; Kido, Y. (Surf. Sci., 1999)

(untitled) - Brunen, J.; Zegenhagen, J. (Surf. Sci., 1997)

(untitled) - Gunhold, A.; Gömann, K.; Beuermann, L.; Kempter, V.; Borchardt, G.; MausFriedrichs, W. (Surf. Sci., 2004)

(untitled) - Gunhold, A.; Beuermann, L.; Gömann, K.; Borchardt, G.; Kempter, V.; MausFriedrichs, W.; Piskunov, S.; Kotomin, E. A.; Dorfman, S. (Surf. Interface Anal., 2003)

(untitled) - Bando, H.; Aiura, Y.; Haruyama, Y.; Shimizu, T.; Nishihara, Y. (J. Vac. Sci. Technol., B, 1995)

(untitled) - Russel, B. C.; Castell, M. R. (Phys. Rev. B, 2008)

(untitled) - Enterkin, J. A.; Subramanian, A. K.; Russell, B. C.; Castell, M. R.; Poeppelmeier, K. R.; Marks, L. D. (Nat. Mater., 2010)

(untitled) - Wang, A.; Yang, F.; Zhang, Z.; Tang, Y.; Feng, J.; Wu, K.; Guo, Q.; Guo, J. (Phys. Rev. B, 2011)

(untitled) - Tanaka, M. (Appl. Phys. A, 2013)

(untitled) - Ono, T.; Shinjo, T. (Surf. Sci., 1999)

(untitled) - Fu, Q.; Wagner, T. (Thin Solid Films, 2002)

(untitled) - Francis, A. J.; Cao, Y.; Salvador, P. A. (Thin Solid Films, 2006)

(untitled) - Silly, F.; Castell, M. R. (Appl. Phys. Lett., 2005)

(untitled) - Kamaratos, M.; Vlachos, D.; Foulias, S. D. (J. Phys.: Condens. Matter, 2008)

(untitled) - Fu, Q.; Wagner, T. (Surf. Sci. Rep., 2007)

(untitled) - Sato, H.; Shinozaki, S. (Surf. Sci., 1970)

(untitled) - Fukaya, K.; Ino, S.; Ogawa, S. (Trans. Jpn. Inst. Met., 1978)

(untitled) - Henry, C. R. (Surf. Sci. Rep., 1998)

(untitled) - Zhang, J.-M.; Wang, D.-D.; Xu, K.-W. (Appl. Surf. Sci., 2006)

(untitled) - Eglitis, R. I.; Vanderbilt, D. (Phys. Rev. B, 2008)

(untitled) - Campbell, C. T. (Surf. Sci. Rep., 1997)

(untitled) - Goodman, D. W. (Surf. Rev. Lett., 1995)

(untitled) - Bäumer, M.; Freund, H.-J. (Prog. Surf. Sci., 1999)

(untitled) - Stroscio, J. A.; Pierce, D. T.; Dragoset, R. A. (Phys. Rev. Lett., 1993)

(untitled) - Köhler, U.; Jensen, C.; Schindler, A. C.; Brendel, L.; Wolf, D. E. (Philos. Mag. B, 2000)

(untitled) - Winterbottom, W. L. (Acta Metall., 1967)

(untitled) - Henry, C. R. (Prog. Surf. Sci., 2005)

(untitled) - Vermout, P.; Dekeyser, W. (Physica (Amsterdam), 1959)

(untitled) - Ueda, R. (Thin Solid Films, 1976)

(untitled) - Le Gressus, C.; Valin, F.; Gautier, M.; Duraud, J. P.; Cazaux, J.; Okuzumi, H. (Scanning, 1990)

(untitled) - Bridger, P. M.; Bandić, Z. Z.; Piquette, E. C.; McGill, T. C. (Appl. Phys. Lett., 1999)

(untitled) - Gao, Y.; Liang, Y.; Chambers, S. A. (Surf. Sci., 1996)

(untitled) - Fu, Q.; Wagner, T. (J. Phys. Chem. B, 2005)

(untitled) - Yeadon, M.; Yang, J. C.; Ghaly, M.; Averback, R. S.; Gibson, J. M. (Mater. Sci. Eng., B, 1999)

(untitled) - Bording, J. K.; Li, B. Q.; Shi, Y. F.; Zuo, J. M. (Phys. Rev. Lett., 2003)

(untitled) - van der Merwe, J. H. (Philos. Mag. A, 1982)